Effect of Sodium Nitroprusside with Plant Growth Regulators on in vitro Propagation and Genetic Stability of ‘Barhee’ Date Palm (Phoenix dactylifera L.) - Al-Mayahi Ahmed Madi Waheed (Journal of Horticultural Research)
Date palm micropropagation still faces many limitations in practical applications due to tissue browning, reduced callus growth and development, low organogenesis and multiplication efficiency, and low rooting rate. This study investigated the effects of sodium nitroprusside (SNP), a source of nitric oxide and plant growth regulators, on the growth attributes and some biochemical constituents of in vitro cultured ‘Barhee’ date palm. The addition of SNP to the culture media was more effective than the individual application of growth regulators regarding callus growth, shoot regeneration, and the number of shoots per jar. The best results (338 mg callus, 80% shoot regeneration, and 17.5 shoots per jar) were obtained in the medium with the addition of 20 μM SNP, plus 90.5 μM 2,4-dichlorophenoxyacetic acid (2,4-D) for callus growth, and 17.7 μM 6-benzylaminopurine (BAP) for shoot regeneration. The above treatment reduced the amount of soluble phenolic compounds in the callus, reducing browning. Effective micropropagation was accompanied by an increase of chlorophyll content and a decrease in the levels of malondialde-hyde (MDA) and hydrogen peroxide (H2O2). The use of 20 μM SNP in combination with 5.37 μM naphthalene acetic acid (NAA) was most effective on root induction and the number of roots per shoot (93.34% and 7.14 roots per shoot). Monomorphic banding patterns obtained in RAPD-PCR and ISSR-PCR in tissue culture-derived and parental plants confirmed genetic stability. Based on these results, nitric oxide can be considered as an intermediary of callus stimulation, adventitious shoot regeneration, and root induction.